2018
DOI: 10.1148/radiol.2018180217
|View full text |Cite
|
Sign up to set email alerts
|

MRI-defined White Matter Microstructural Alteration Associated with Soccer Heading Is More Extensive in Women than Men

Abstract: Purpose To examine the role of sex in abnormal white matter microstructure after soccer heading as identified by using the diffusion-tensor imaging (DTI) metric fractional anisotropy (FA). Materials and Methods In this prospective cross-sectional study, 98 individuals who were enrolled in a larger prospective study of amateur soccer players (from 2013 to 2016) were matched 1:1 for age and history of soccer heading in the prior 12 months. Among the subjects, 49 men (mean age, 25.7 years; range, 18-50 years) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 45 publications
2
42
0
1
Order By: Relevance
“…Number of lifetime concussions was not determined as a significant confounder in the models; however, Met (+) players demonstrated a borderline trend toward a greater number of lifetime concussions; a fact that may have contributed to our results. Likewise, we have previously reported gender differences in DTI outcomes from soccer heading (14). Though we adjusted for gender in our analyses, we were not powered to detect a heading * gender * BDNF Val 66 Met interaction; which limits our ability to address the combined effect of the Met allele and gender on white matter abnormalities from soccer heading.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Number of lifetime concussions was not determined as a significant confounder in the models; however, Met (+) players demonstrated a borderline trend toward a greater number of lifetime concussions; a fact that may have contributed to our results. Likewise, we have previously reported gender differences in DTI outcomes from soccer heading (14). Though we adjusted for gender in our analyses, we were not powered to detect a heading * gender * BDNF Val 66 Met interaction; which limits our ability to address the combined effect of the Met allele and gender on white matter abnormalities from soccer heading.…”
Section: Discussionmentioning
confidence: 93%
“…HeadCount-12mo. Questionnaire: HeadCount-12mo is a questionnaire that estimates their total number heads in the prior 12-months [refer to Levitch et al 9and Rubin et al (14) for a detailed explanation of Head Count-12mo]. In brief, participants are asked a series of questions pertaining to their soccer play during practice and competition in indoor and outdoor settings: (1) the number of months per year active in each setting; (2) the average number of competitive soccer games per week; (3) the average number of headers per game; (4) the average number of practices per week; (5) the average number of headers per practice.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…B. beim Boxen oder American Football erhebliche Ausmaße annehmen und das weitere Schicksal der Sportler bestimmen können [49]. Auch nach Kopfbällen, weniger nach Tackling, im Fußball hat man inzwischen im Kernspin Hirnschäden gefunden, die bei Frauen ausgeprägter waren als bei Männern [50]. In entsprechenden Leitlinien wird noch nicht auf EPA und DHA eingegangen [51].…”
Section: Kognitionunclassified
“…For example, in 2002 the inquest into the English footballer Jeff Astle who died aged 59 with early-onset dementia found that repeated heading of a heavy leather football had contributed to his illness. However, supported by improved epidemiological studies 2,3 and more accurate imaging techniques that can identify sub-clinical brain cell injury, an evidence base is emerging that confirms this relationship and in particular identifies children 4 and women 5 to be at particular risk.…”
Section: Long-term Implicationsmentioning
confidence: 99%